Diagnóstico de insuficiencia renal y su incidencia en los problemas de pareja en una mujer de 55 años de la Unidad de Hemodiálisis Los Ríos - Mayorga Chango, Lilibeth Estefania (2022)
Kidney failure in a disease that is progressing faster and faster, can be developed by anyone independently. If a couple does not learn to adapt to the new lifestyle, it will bring negative consequences, many times the emotional field is not taken enough importance. This case study focuses on psychological involvement, which aims to determine the incidence of a diagnosis of kidney failure in couple problems in a 55-year-old woman from the Los Ríos hemodialysis unit. In which issues related to kidney failure, its causes, its treatment, as well as couples problems, coping with a sick family member, recommendations will be discussed. In order to carry it out, it was necessary to use various techniques with their respective tools, which were very useful in the therapeutic process, in order to meet the stated objective. Subsequently, the diagnosis was identified, in order to establish a therapeutic plan, with the aim of improving the environment in their marital relationship, achieving a calmer and more stable environment.